METODE PEMBELAJARAN KUTUB AL-TURATS PONDOK PESANTREN DI SALATIGA: ANALISIS DALAM PERSPEKTIF SQ3R - Roviin Roviin; Muhammad Hafidz (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2024)
Learning kutub al-turats will become more interesting if it is carried out using various methods as implemented in school or madrasa. One method of learning to texts reading is SQ3R (Survey, Question, Read, Recite, Review). This study aims to describe the kutub al-turats learning method at pesantrens in Salatiga and the implementation of the SQ3R steps in learning kutub al-turats. The data was collected with observation, interview, and documentation, while data analysis was carried out through data reduction, data display, and conclusion. The results of the study show that the methods used in learning kutub al-turats are classified into two types, namely the main and complementary methods. The main methods are bandongan and sorogan, complemented by other methods such as lectures, practices, kilatan, lalaran, bahtsul masa’il, setoran, yanbu'a and talqin. Pesantrens in Salatiga have not been maximal in implementing the steps of the SQ3R method in learning kutub al-turats. Learning kutub al-turats in pesantren should using a variety of methods without eliminating the bandongan and sorogan methods as the main methods. Pesantren should using the SQ3R method which is considered quite systematic in learning kutub al-turats. This method can be combined with the sorogan, bandongan or other methods.